A experiência com o software Graphogame na criação da matriz de requisitos para auxiliar educadores na escolha de softwares educacionais para a alfabetização de crianças - Cavalcante, Erika Maria da Silva (2025)
The beginning of the 21st century was marked by the development of numerous educational software programs, and children's literacy followed suit. In Finland, a group of researchers used their expertise in the areas of language and cognition to create a virtual game to support children's reading learning, called GraphoGame (GG). After being used in several countries, GG was made available in a Brazilian Portuguese version by the Ministry of Education in 2020, as a result of the National Literacy Policy (PNA) in force at the time. Publications regarding case studies and other experiences with GraphoGame indicate that, in most cases, the game meets its purposes, partially or fully. The objective of this research was to create a matrix of requirements to help educators choose literacy software for children. To this end, it was decided to conduct fieldwork that involved interventions with children in the 2nd grade of elementary school in the city of Fortaleza, in the state of Ceará. In addition, a technical evaluation of GraphoGame was carried out from a software engineering perspective. The technical analysis showed that, overall, GG meets the requirements to be considered a quality tool. The results of the practical research, in turn, indicated that the playful functionalities provided by GG are excellent for attracting children's interest. Regarding the pedagogical aspect, the software stands out for its accessibility and effectiveness, working offline and ensuring safe use in environments without connectivity. With an attractive design, adequate visual and sound stimuli, interactive functionalities and diverse playful scenarios, it maintains children's interest and enchantment. The quality of the phoneme pronunciations reinforces its potential as an innovative pedagogical tool. In addition to these positive points, aspects that could be improved were observed to ensure that it is in line with the demands of current education. In parallel with the evaluation of the GraphoGame software, this research also presents discussions on literacy in Brazil (history, data, challenges and public policies) and the use of digital technologies in education, with some of its main theoretical references, in addition to its public policies and guidelines. The matrix, called AlfaPráticas, was created based on the technical and pedagogical aspects of the GG analyzed to assist educators in choosing educational software for children in the literacy phase. The matrix and other related content are housed in a virtual environment created specifically for this purpose.